2008
DOI: 10.1016/j.immuni.2008.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 Promotes Autoimmunity by Triggering a Positive-Feedback Loop via Interleukin-6 Induction

Abstract: Dysregulated cytokine expression and signaling are major contributors to a number of autoimmune diseases. Interleukin-17A (IL-17A) and IL-6 are important in many disorders characterized by immune self-recognition, and IL-6 is known to induce the differentiation of T helper 17 (Th17) cells. Here we described an IL-17A-triggered positive-feedback loop of IL-6 signaling, which involved the activation of the transcription factors nuclear factor (NF)-kappaB and signal transducer and activator of transcription 3 (ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
456
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 509 publications
(495 citation statements)
references
References 61 publications
17
456
0
2
Order By: Relevance
“…Since some ILs including IL1b and IL6 are transcriptionally regulated by NF-kB, which may create a positive feedback loop to chronically activate the signaling pathway [36,37], we further tested whether IL1b and IL6 could be self-regulated via the NF-kB signaling. Interestingly, the attenuation of NF-kB suppressed the expressions of IL1b and IL6 at both mRNA and protein levels in the supernatant ( Supplementary Fig.…”
Section: Il1b and Il6 Served As The Nf-jb Signaling Potential Regulatmentioning
confidence: 99%
“…Since some ILs including IL1b and IL6 are transcriptionally regulated by NF-kB, which may create a positive feedback loop to chronically activate the signaling pathway [36,37], we further tested whether IL1b and IL6 could be self-regulated via the NF-kB signaling. Interestingly, the attenuation of NF-kB suppressed the expressions of IL1b and IL6 at both mRNA and protein levels in the supernatant ( Supplementary Fig.…”
Section: Il1b and Il6 Served As The Nf-jb Signaling Potential Regulatmentioning
confidence: 99%
“…In addition to its effects on antibody production, IL-6 has a strong stimulatory effect on the growth of mouse plasmacytoma [13] and human myeloma cells [12]. Recently, Ogura et al [14] have reported that IL-17 promotes autoimmunity by triggering a positive-feedback loop through the induction of IL-6. In the study reported herein, we generated transgenic (Tg) mice that overexpressed RORγt and showed that RORγt Tg mice displayed excessive IL-6 production, the development of plasmacytosis, and autoantibody production.…”
mentioning
confidence: 99%
“…One mechanism associated with this development and specific to nonimmune cells, such as synovial cells, fibroblasts, and endothelial cells, is an NF-kB activator, the inflammation amplifier (formerly IL-6 amplifier) (15), which is activated by a simultaneous stimulation of NF-kB and STAT3. The main functional molecules of the inflammation amplifier are chemokines and growth factors, which deregulate local homeostasis via an accumulation of various immune cells and proliferate various regional cells, whereas IL-6 mainly acts as fuel to maintain the activation of STAT3 (16,17).…”
Section: B Reakpoint Cluster Region (Bcr) Protein Is a Unique Kinasementioning
confidence: 99%
“…We previously reported an inflammation-inducing mechanism, called the inflammation amplifier, in nonimmune cells such as synovial cells and endothelial cells (15), which is activated by a simultaneous stimulation of NF-kB and STAT3 and involved in the pathogenesis of several inflammatory disease models (17)(18)(19). By genome-wide screenings, we have identified that BCR is one of the positive regulators of the inflammation amplifier (17).…”
Section: Bcr Is Critical For Nf-kb Activation In Vivo and In Vitromentioning
confidence: 99%